Characterization of chitosan/α-lactalbumin nanocomplex particle and its encapsulation for retinol. (February 2023) - Jiang, Zhanmei; Li, Jinzhe; Chen, Wei; Hussain, Muhammad Altaf; Wei, Xuan; Bilawal, Akhunzada; Hou, Juncai
Abstract: Chitosan (Ct) and α-lactalbumin (ALa) were applied as the carriers, their biopolymer nanoparticle was designed to encapsulate retinol (VA). Zeta potential and turbidity measurements, demonstrated that the most suitable pH value in the formation of Ct/ALa nanoparticle was 6.0, and its optimal Ct/ALa mass ratio was 1:4. At this ratio, scanning electron microscopy (SEM) of Ct/ALa nanoparticle showed that Ct was coated on the surface of ALa/VA as a shell. Meanwhile, the encapsulation efficiency (EE) and loading capacity (LC) of above nano-sized Ct/ALa particle for VA were 82.22 ± 1.78% and 3.13 ± 0.12%, respectively. Moreover, Ct/ALa nanoparticle not only improved the storage stability of VA, but also protected VA from the destruction of simulated gastrointestinal juice to a certain extent during in vitro digestion. Information from this study could supply the novel opinion for the protection and delivery of photosensitive bioactive substances (VA) in functional dairy-based product. Graphical abstract: Image 1 Highlights: Chitosan (Ct)/α-lactalbumin (ALa) was applied as novel material to encapsulate VA. Ct was coated on the surface of ALa/VA as a spherical shell for protecting VA. Ct/ALa nanoparticle could protect VA from the destruction of gastrointestinal juice.